2009
DOI: 10.1590/s0102-33062009000100030
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento do cáudice e fenologia de Dicksonia sellowiana Hook. (Dicksoniaceae) no sul do Brasil

Abstract: RESUMO -(Crescimento do cáudice e fenologia de Dicksonia sellowiana Hook. (Dicksoniaceae) no sul do Brasil). No sul e sudeste do Brasil, a samambaia arborescente Dicksonia sellowiana Hook. é ainda extraída ilegalmente de remanescentes florestais para uso da capa fibrosa do seu cáudice, bem como para cultivo como planta ornamental. No presente trabalho, o crescimento do cáudice, a produção, expansão e senescência de frondes, bem como a formação e liberação de esporos de D. sellowiana foram estudados com base na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 36 publications
(42 reference statements)
5
22
0
21
Order By: Relevance
“…It is likely that the variation of approximately 3.5 h in the photoperiod over the course of a year in the coastal region of Rio Grande do Sul, together with the direct effects of changes in temperature, triggers predictable physiological responses in several species (Marchioretto et al 2007), as was observed for C. corcovadensis in the present study, as well as and for C. atrovirens and Dicksonia sellowiana in the studies conducted by Schmitt et al (2009) and Schmitt & Windisch (2012), respectively. In a study of 16 fern species in a subtropical broadleaf forest in northeastern Taiwan, Lee et al (2009) reported that leaf senescence, spore maturation and spore release all presented significant positive correlations with temperature but not with precipitation, which is in agreement with our findings for C. corcovadensis.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…It is likely that the variation of approximately 3.5 h in the photoperiod over the course of a year in the coastal region of Rio Grande do Sul, together with the direct effects of changes in temperature, triggers predictable physiological responses in several species (Marchioretto et al 2007), as was observed for C. corcovadensis in the present study, as well as and for C. atrovirens and Dicksonia sellowiana in the studies conducted by Schmitt et al (2009) and Schmitt & Windisch (2012), respectively. In a study of 16 fern species in a subtropical broadleaf forest in northeastern Taiwan, Lee et al (2009) reported that leaf senescence, spore maturation and spore release all presented significant positive correlations with temperature but not with precipitation, which is in agreement with our findings for C. corcovadensis.…”
Section: Discussionsupporting
confidence: 62%
“…The mean annual number of mature leaves was equivalent among the three years evaluated. Therefore, tree ferns seem able to maintain a relatively stable number of leaves over a long period of time, as observed for Dicksonia sellowiana (Schmitt et al 2009) and C. atrovirens (Schmitt & Windisch 2012).…”
Section: Monitoredmentioning
confidence: 77%
See 3 more Smart Citations